2020
DOI: 10.3389/fbuil.2020.00040
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Identification as a Tool to Constrain Numerical Models for Structural Analysis of Historical Buildings

Abstract: Operational modal analysis (OMA), also known as output-only or ambient vibration test (AVT), has become in last decades a powerful approach for a wide range of applications in the field of civil engineering. When historical structures are investigated this approach is particularly appealing avoiding shaking the structure artificially. This paper discusses the assessment of the dynamic behavior of the Baptistery of San Giovanni in Firenze (Italy). Based on experimental results obtained through a temporary netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Lately, a simplified numerical model is developed and the uncertain structural parameters are calibrated using a classical model updating technique. In comparison with other research [17][18][19][20][21][22][23][24], the developed procedure focuses specifically on the merging of architectonic information and the FE model updating to develop simplified numerical models that should be integrated in the context of a digital twin for architectural preservation [25,26]. This paper illustrates the application of the proposed procedure-including historical and architectural investigation supplemented by dynamic testing-in the structural evaluation of the Zuccaro's tower (or Torre degli Zuccaro, in Italian) in Mantua (Italy) (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 67%
“…Lately, a simplified numerical model is developed and the uncertain structural parameters are calibrated using a classical model updating technique. In comparison with other research [17][18][19][20][21][22][23][24], the developed procedure focuses specifically on the merging of architectonic information and the FE model updating to develop simplified numerical models that should be integrated in the context of a digital twin for architectural preservation [25,26]. This paper illustrates the application of the proposed procedure-including historical and architectural investigation supplemented by dynamic testing-in the structural evaluation of the Zuccaro's tower (or Torre degli Zuccaro, in Italian) in Mantua (Italy) (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 67%
“…The study [22] presented an identification problem for a reinforced concrete, tall building based on model updating and experimental modal analysis. In [23], the authors showed the dynamic identification of the Baptistery of San Giovanni in Firenze (Italy) based on OMA and frequency domain decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies in the literature on applications of finite-element models to study dynamic analyses with use of experimental measurements; a large part of the scientific literature concerns slender structures, such as towers and minarets [4][5][6][7][8]. There are also works regarding ancient Roman constructions, such as the Colosseum [3,9,10], the Basilica of Maxentius [2], the Baths of Diocletian [11], the Trajan Arch [12], the Circus Maximum [13], the Frontinus Gate [14], the Verona Arena [15], and the so-called Temple of Minerva Medica [16,17]; the main focus of these studies is dynamic identification, thus processing of site-recorded data to extract the modal features of these constructions.…”
Section: Introductionmentioning
confidence: 99%